Categorizing labour: How platforms and workers co-construct digital markets - Albert, J (2023)
This project is an economic sociology perspective on the construction of online labour markets. I investigate classifications of labour as tools for market organization and sites of struggle between workers and platform firms. Platform firms use classificatory devices such as recommender algorithms or quality labels to order their marketplaces and extract value. For millions of remote gig workers being classified matters because it directly affects their livelihoods. To investigate this tension, I ask how and to what effect workers are classified in online labour markets. I address this question based on interface walk-throughs, worker interviews, and a survey across two online freelancing platforms. I problematize the view that classes in digital markets are primarily assigned automatically based on platform-specific, individual-level data, and thus removed from the social practices of those classified. My first study shows how platform firms use classification systems to the effect of placing workers into discrete market categories. Consequential digital boundaries result from manual choices as well as automated algorithms. My second study theorizes quality labels that platforms attach to workers’ profiles as market devices. I propose that these devices co-construct worker quality in the hiring process. To evaluate workers’ experiences prior to platform work, administrators strategically fall back on conventional hiring techniques. My last study shows that centralized classification systems are circular and incomplete. It requires workers’ informal categorical practices to complete the loop. By integrating these studies, I arrive at my thesis that classifications of labour remain embedded in the social practices of the classified workers. By putting the social back into classification, I show how online markets are co-constructed by workers and platform firms alike. My research makes visible platform firms’ classificatory power and their implicit value judgments on whose work counts, while also uncovering categorical work as an underappreciated form of worker agency.